Analisis Motivasi, Faktor Sosial, Impulse Buying, Kepercayaan Merek, dan Word of Mouth: Studi Fenomenologis pada Seminar Manajemen Pemasaran - Widyadhana Candraningtias; Krismonika Hidayat; Anjastanara Pasae (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study explores the underlying meanings of students’ experiences related to motivation, social factors, brand trust and image, and word of mouth in shaping impulse buying behavior in the digital era. Unlike most previous research employing quantitative methods, this study adopts a qualitative phenomenological approach supported by a Likert-scale perception instrument to elicit experiential narratives. The participants consisted of students enrolled in the Marketing Management Seminar course. Data were collected through Likert-scale questionnaires, short open-ended interviews, and field observations. Descriptive results show that motivation (mean = 4.25), brand trust and image (mean = 4.17), and word of mouth (mean = 4.01) fall into the high category, while social factors (mean = 3.73) and impulse buying (mean = 3.74) are moderately high. The qualitative findings highlight motivation as the primary driver of spontaneous purchasing, influenced by emotional needs, trends, and digital promotional stimuli. Word of mouth acts as an informational catalyst that accelerates decision-making, whereas social factors and brand trust provide psychological assurance in impulsive purchases. Overall, this study deepens understanding of student consumption dynamics and contributes to consumer behavior research within higher education contexts.